Fostering cognitive model reasoning and conceptual understanding of immunoglobulin concepts through computer animation with case-based pedagogy - Basit, Supachai Amphay (Animo Repository, 2009)
This study intends to foster cognitive model reasoning and conceptual understanding of immunoglobulin concepts by using case-based pedagogy and computer animation as intervention tools. The efficacy of the interventions was determined using triangulate assessments in the forms of the Immunoglobulin Concept Test (ICT), Cognitive Model Reasoning and Clinical Case Analysis. All third year (N=23) and fourth year (N=6) medical technology students participated in the pre-intervention phase where the pre-test of expert and reliability validated ICT was given to identify participants of the study in the next phase. The top, median and lowest scorers per year level (N=6) were identified to participate in the pre-intervention cognitive model reasoning and clinical case analysis. In the intervention phase, the identified participants were allowed to watch computer animations and participate in the roundtable discussion of clinical case questions wherein they were tasked to discuss their pre-intervention answers and analyze laboratory data to the clinical cases. The ICT post test, cognitive model reasoning and clinical case analysis were also done in the post intervention phase. The findings indicate significant improvement of the ICT post test scores after the interventions were given, Z(6) = 2.032, p = .042. Moreover, the findings of the cognitive model reasoning indicate remarkable improvement after the interventions were given as shown by the corrections of alternative concepts of the cognitive models. There was also a significant difference between the pre- and post- cognitive model scores as evaluated by a panel of experts based on the provided scoring rubrics, Z(6) = -2.207, p = .027. Additionally, seven of the ten identified main alternative concepts in case-based pedagogy were corrected in the post-intervention phase. The learners responses to the clinical case questions became more conceptually correct and explicit as substantiated by clinical case content analysis and the extracted main themes when analyzed using the SPSS Text Analysis Survey for Qualitative Data. Thus, this study validates the potential uses of computer animation and case-based pedagogy in providing cognitive model reasoning and conceptual understanding of immunoglobulin concepts in immunology.